THE EFFECT OF EDUCATION ON INCREASING COMMUNITY KNOWLEDGE RELATED TO SELF-MEDICATION - Fasyir, Syaima Rihan (Berkala Ilmiah Mahasiswa Farmasi Indonesia, 2023)
Introduction: Self-medication is an attempt to treat minor ailments independently before consulting to a doctor. In Indonesia, self-medication is always increasing every year. Based on data from the Central Statistics Agency (BPS), the percentage of the Indonesian population who self-medicated in 2020-2022 is 72.19%, 84.23%, and 84.34% respectively. Self-medication that is carried out has the potential for errors in disease diagnosis, delays in searching for the necessary treatment, inaccurate doses, and wrong administration methods. Therefore, knowledge is needed to carry out self-medication so as to prevent medication errors. Methods: The method used in this research is a literature study from various journals and websites using Mendeley and Harzing’s Publish or Perish as sources (digital libraries). Result: The focus group discussion (FGD) method has a significant effect on increasing public knowledge about self-medication with the posttest scores of all respondents experiencing an increase indicating the range of assessments is in the good category. Then in the second article using online media there is a sufficient percentage of 4.48%. However, this education can contribute to increasing public knowledge about self-medication. Education using leaflet media and the Active Individual Learning Method (CBIA) method can increase public knowledge about self-medication. Conclusion: Education to the public can increase knowledge about self-medication. Of the three methods used, the method that most increased public knowledge about self-medication was focus group discussions (FGD) by holding discussions so that participants could be more active and understand the material more easily.